2020
DOI: 10.32479/ijeep.8337
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Pollution Control Caused by Exhaust Gas Emissions in Developing Country Cities in Public Policy Law Perspective

Abstract: The increase in air pollution in cities generally comes from motor vehicle emissions. The purpose of this paper is to analyze the regulation and role of the city government through public policy to control air pollution. The regulation of air pollution control with legislation has regulated fuel standards, air capacity, negative impacts on the environment due to the use of space, and the exhaust emission threshold. Interrelated planning and regulatory actions can lead to significant reductions in pollutants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The importance of public engagement in air pollution reduction is evident. Research has indicated that the dissemination of information to the general population regarding air pollution and its associated impacts has the potential to result in a decrease in levels of air pollution [16,17]. The involvement of the general public can also have an impact on the emission patterns exhibited by both people and corporations [18].…”
Section: To Effectively Combat Air Pollution the General Population M...mentioning
confidence: 99%
“…The importance of public engagement in air pollution reduction is evident. Research has indicated that the dissemination of information to the general population regarding air pollution and its associated impacts has the potential to result in a decrease in levels of air pollution [16,17]. The involvement of the general public can also have an impact on the emission patterns exhibited by both people and corporations [18].…”
Section: To Effectively Combat Air Pollution the General Population M...mentioning
confidence: 99%
“…The high levels of exhaust gas emissions in vehicles, of course, requires the need for technology to measure vehicle exhaust gases to reduce the impact of air pollution [4] [5]. However, the procurement of exhaust emission test equipment is still expensive, so only certain class workshops have this tool and the cost of testing exhaust emissions is also expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor and outdoor air pollution is currently an important concern because it can cause health problems, it is known that around 4 million deaths occur due to indoor pollution and 3 million deaths come from outdoors [4,5] Around 17,600 people out of 22,000 (80%) members of Polda Metro Jaya have ARI. most of them work in the field for a long time, 70% of which is related to the high pollution in Jakarta that comes from motor vehicles [6]. Knowledge and understanding of ARI are important because its spread is very wide, its complications are dangerous, and cause loss of working days, even resulting in death (especially pneumonia).…”
Section: Introductionmentioning
confidence: 99%